Foreign Direct Investment from Emerging Markets. Theory and Practice - Gudowski, Janusz; Piasecki, Ryszard (Comparative Economic Research. Central and Eastern Europe, 2020)
This text presents a critical review of theoretical approaches to Foreign Direct Investment. Since, in recent years, the contribution of emerging markets to FDIhas increased (especially on less advanced markets), it is interesting to define how the existing theory can explain the new players phenomenon on these markets. There are two hypotheses considered: one – the existing theoretical explanations of FDI are limited and, today, even historical; second – the essence of the comparative advantage of FDI from emerging markets is a smaller technological and organizational distance between investors and less developed host markets. The discussion is illustrated by Chinese and Indian FDI experience to support the authors’ assumptions.